The Utopia of a Single Race for the Nation. Mestizaje, Indigenism and Hispanophilia in Postrevolutionary Mexico - González Salinas, Omar Fabián (Universidad Pedagógica y Tecnológica de Colombia, 2016)
This article studies different projects for the construction of Nation during postrevolutionary Mexico, which attempted to establish a single race in order to ensure a promising future for the Nation. We will examine the racial ideas of three of the most important intellectuals of this time, as well as the official discourse with which the State demostrated what was the “mexican race”. We use the category “utopia” in the study, in defining a project set in the future that emerges from the criticism and necessity to overcome the problems of the present through radical transformation. This method is considered pertinent, due to the fact that the racial debates examined had a special interest in the future, proposing different paths to reconstruct the nation. Finally, we make a balance between the long-term success or failure of the pairing of race and nation in Mexico.